Engaging Biological Sciences Students in the Development of Employability Skills through Creative Teaching and Peer Reviewed Action Plans - Ian J Turner (Association for Learning Development in Higher Education (ALDinHE), 2012)
In this article the authors describe how creative learning experiences can be developed within the curriculum to enhance employability skills and engage the students in their personal development planning. A novel approach using a subject specific employability exercise and the production of peer critiqued action plans is described along with a summary of studentsÃ¢â¬â¢ responses.